Genome-Wide Identification, Classification, and Expression Analysis of Amino Acid Transporter Gene Family in Glycine Max - Cheng, Lin; Yuan, Hong-Yu; Ren, Ren; Zhao, Shi-Qi; Han, Ya-Peng; Zhou, Qi-Ying; Ke, Dan-Xia; Wang, Ying-Xiang; Wang, Lei (Frontiers in Plant Science, 2016)
Amino acid transporters (AATs) play important roles in transporting amino acid across cellular membranes and are essential for plant growth and development. To date, the AAT gene family in soybean (Glycine max L.) has not been characterized. In this study, we identified 189 AAT genes from the entire soybean genomic sequence, and classified them into 12 distinct subfamilies based upon their sequence composition and phylogenetic positions. To further investigate the functions of these genes, we analyzed the chromosome distributions, gene structures, duplication patterns, phylogenetic tree, tissue expression patterns of the 189 AAT genes in soybean. We found that a large number of AAT genes in soybean were expanded via gene duplication, 46 and 36 GmAAT genes were WGD/segmental and tandemly duplicated, respectively. Further comprehensive analyses of the expression profiles of GmAAT genes in various stages of vegetative and reproductive development showed that soybean AAT genes exhibited preferential or distinct expression patterns among different tissues. Overall, our study provides a framework for further analysis of the biological functions of AAT genes in either soybean or other crops.